2015
DOI: 10.1002/sce.21204
|View full text |Cite
|
Sign up to set email alerts
|

Fostering Today What is Needed Tomorrow: Investigating Students’ Interest in Science

Abstract: This paper investigates the structure of German sixth‐grade students’ interest in science (N = 474; age 11–12 years) by considering different subject‐related contexts (biology, chemistry, and physics) and different activities. Confirmatory factor analysis models were designed to validate the hypothetical structure of interest, connecting the whole spectrum of early school science with Holland's RIASEC model, and revealed that students’ interest in science is best described by a cross‐classified model with late… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
40
1
13

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 51 publications
(60 citation statements)
references
References 95 publications
(154 reference statements)
6
40
1
13
Order By: Relevance
“…The RIASEC + N model acknowledges all seven dimension as meaningful elements of science instruction and thus provides a more multifarious picture of (school) science than the rather stereotypical categorization of science as an exclusively investigative endeavor in the original model (Holland, ). So far, evidence for the hypothesized structure has been found (Blankenburg et al, ), but no findings in connection to achievement have been reported. Due to its differentiation and decontextualized operationalization, the model allows precise comparisons of students' interests over longer time spans.…”
Section: Theoretical Backgroundmentioning
confidence: 97%
See 3 more Smart Citations
“…The RIASEC + N model acknowledges all seven dimension as meaningful elements of science instruction and thus provides a more multifarious picture of (school) science than the rather stereotypical categorization of science as an exclusively investigative endeavor in the original model (Holland, ). So far, evidence for the hypothesized structure has been found (Blankenburg et al, ), but no findings in connection to achievement have been reported. Due to its differentiation and decontextualized operationalization, the model allows precise comparisons of students' interests over longer time spans.…”
Section: Theoretical Backgroundmentioning
confidence: 97%
“…Additional aspects such as subject contents and themes, contexts (Häussler, Hoffmann, Langeheine, Rost, & Sievers, ), or activities (Schmidt, Rosenberg, & Beymer, ; Swarat et al, ) may be indispensable for describing profiles of interest in science. Such an integrated approach is provided by the adapted version of Holland's RIASEC model, allowing more precise insights into the development of interest and its connection to learning (Blankenburg, Höffler, & Parchmann, ; Dierks et al, , ). The adapted version of the RIASEC model takes up the multifaceted structure of the original model, that is, the categorization of interests into different personality types (according to which scientists would be allocated to the dimension investigative solely), but instead of focusing on vocational interests, it describes interest in different types of school science activities.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 2 more Smart Citations
“…Lastly, self-concept is correlated with gender. Often, boys were found to have a higher academic self-concept in mathematics (Meece, Wigfield, & Eccles, 1990) and science (Blankenburg, Höffler, & Parchmann, 2015;Wilkins, 2004) while girls' academic self-concept in languages was superior (Crain, 1996;Köller et al, 2000;Marsh & Yeung, 1997), which coincides with typical interest distributions between girls and boys (Baumert & Köller, 1998). However, the magnitude of those gender gaps differs across the world (Wilkins, 2004).…”
Section: Theory and Current Researchmentioning
confidence: 92%